2019
DOI: 10.1080/1088937x.2019.1578287
|View full text |Cite
|
Sign up to set email alerts
|

The Arctic in tourism: complementing and contesting perspectives on tourism in the Arctic

Abstract: The economic and political importance of the Arctic has grown considerably in recent decades, and the region's role and visibility in tourism has also significantly increased. The idea of Arctic tourism has been discussed in academia for a long time, but there is no consensus on the definition of the concept. This review paper aims to discuss different perspectives on tourism in the Arctic by utilising literature and selected examples. The outlined perspectives are spatial, produced and experienced Arctic tour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 47 publications
0
25
0
2
Order By: Relevance
“…SDG 8 furthermore refers specifically to sustainable tourism (8.9); also mentioned under SDG 12b. Some parts of the Arctic are currently experiencing a major increase in tourism such as in the case of Iceland, with both social and environmental impacts, raising questions about the sustainability of this industry [61,62]. In scenario workshops, tourism has been mentioned both as an opportunity for new jobs and as a challenge to local livelihoods and the capacity of existing infrastructure.…”
Section: Sdg 8 Promote Sustained Inclusive and Sustainable Economicmentioning
confidence: 99%
“…SDG 8 furthermore refers specifically to sustainable tourism (8.9); also mentioned under SDG 12b. Some parts of the Arctic are currently experiencing a major increase in tourism such as in the case of Iceland, with both social and environmental impacts, raising questions about the sustainability of this industry [61,62]. In scenario workshops, tourism has been mentioned both as an opportunity for new jobs and as a challenge to local livelihoods and the capacity of existing infrastructure.…”
Section: Sdg 8 Promote Sustained Inclusive and Sustainable Economicmentioning
confidence: 99%
“…The Arctic tourism as a special branch of tourism market has emerged during the last three decades (Viken 2011) and both regions are a good example of tourismoriented economies. As shown by Saarinen and Varnajot (2019), the demand for "Arctic" experience is still high. On one hand, Øian et al (2018) identified the preserved nature and experience of solitude as an important reason for visiting the Arctic.…”
Section: Discussionmentioning
confidence: 99%
“…Authenticity is also a layered concept, which depends on the group as well as the relation to the object (Goulding and Derbaix 2019). Furthermore, the discussion also includes a conceptualization of authenticity as experienced authentic by the tourists, but inauthentic from a research viewpoint (Saarinen and Varnajot 2019). Negative authenticity is also studied from the constructivist viewpoint; it is 'the true but unacceptable part of the destination' (Zhou et al 2018, 60) such as poverty.…”
Section: Authenticitymentioning
confidence: 99%